HARMONIZATION IS THE ONLY “GAME” IN TOWN; ACTUALIZING THE FUNCTIONALITY OF VITAL ISLAMIC FINANCIAL INSTITUTIONS: A CASE OF WAQFS IN NIGERIA - Saidu, Oluwaseun Sulaiman; Cizakca, Murat; Wilson, Rodney (Jurnal Syariah, 2021)
While it is true that more often than not, constitutional democracies might enshrine freedom of religion and thus provide for equal treatment of all religions within a given state, the Islamic characterization of the waqf institution transcends the subsisting limits allowed for in the not-for profit legal infrastructure including their taxation exemption provisions in the Nigerian state. According to modest statistics, Nigeria is home to about 100 million Muslims but her governing laws are at best described as secular. The objective of this research is therefore to harmonize the Islamic law of waqf institution and the extant not-for-profit laws in Nigeria such that the institution can function within the Nigerian state without infringing on the Islamic Shariah whilst at the same time complying with the constitutional dictates of the country. The merits of such an exercise are numerous. It could readily be replicated in other non-Muslim jurisdiction across the world. Nigeria being the largest economy in Africa, the dividends of such an exercise would cascade across the continent consisting mainly so called developing countries.